Pengaruh Independensi, Keanggotaan, Kompetensi, dan Gender Komite Audit Terhadap Audit Delay - Santiani, Komang Novika; Muliartha, Ketut (E-Jurnal Akuntansi; Vol 23 No 1 (2018)DO - 10.24843/EJA.2018.v23.i01.p17, 2018)
The establishment of an audit committee is one of the implementation of GCG application. Audit Committee is formed by a board of commissioners who are in charge to assist the board of commissioners in controlling the company's financial reporting process. With the presence of the audit committee, it is expected that there will be no fraud, because the audit committee will be able to mediate the conflict between both of the parties so it can improve the quality of the financial’s report and accelerate the audit process by external parties. This study aims to determine the influence of independence, membership, competence, and gender of audit committee on Audit Delay. The research was conducted at manufacturing company that listed on Indonesia Stock Exchange 2014-2016. The sample of the research is 90 companies with purposive sampling method. Data analysis technique used is multiple regression analysis. The results of the analysis found that audit committee membership negatively affected audit delay, while the independence, competence, and gender of audit committee did not affect audit delay. Keywords : independence, membership, competence, gender, audit delay.